Intrazerebrale Blutung: „hot topics“ - Sprügel, Maximilian; Huttner, Hagen (Der Nervenarzt, 2019)
Significant advances in the acute treatment of patients with intracerebral hemorrhage (ICH) have been achieved in recent years. While many randomized trials have provided neutral results, important findings have been generated for the design of follow-up studies. Furthermore, a number of observational studies have been published, which in turn provide the basis for further methodologically stronger investigations. The focus is on avoidance of early bleeding progression, which can be influenced by blood pressure management and hemostasis. Furthermore, ICH surgery may experience a renaissance through minimally invasive techniques. In addition, perihemorrhagic edema and its pharmacological modulation are becoming increasingly more important. Optimal treatment of ventricular involvement is continuing to develop dynamically. Finally, long-term antithrombotic treatment has been intensely studied in observational analyses and is currently being investigated in randomized trials. This article addresses these most relevant topics in acute and long-term treatment of ICH patients and provides an overview of current debates in these areas of treatment.
CRIS-Team Scopus Importer:2019-08-27
Keywords: Anticoagulation; Hematoma growth; Minimally invasive surgery; Perihemorrhagic edema; Ventricular hemorrhage